Generowanie obcości, czyli recenzja współczesnej polskiej szkoły - Stanek, Bartosz (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The article suggests the need for education, which is free of indoctrination and imposition of authority. Changes that occurred in the Polish educational system during last twenty five years created a subtle form of indoctrination. In such situation an ethical education becomes especially necessary to develop in pupils critical thinking and shape the humanistic attitude.